2013
DOI: 10.1021/jp404979y
|View full text |Cite
|
Sign up to set email alerts
|

riDOM, a Cell-Penetrating Peptide. Interaction with DNA and Heparan Sulfate

Abstract: DNA condensation in the presence of polycationic molecules is a well-known phenomenon exploited in gene delivery. riDOM (retro-inverso dioleoylmelittin) is a cell-penetrating peptide with excellent transporter properties for DNA. It is a chimeric molecule where ri-melittin is fused to dioleoylphosphoethanolamine. The physical-chemical properties of riDOM in solution and in the presence of DNA and heparan sulfate were investigated with spectroscopic and thermodynamic methods. Dynamic light scattering shows that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
0
10
1
Order By: Relevance
“…Our results revealed that this retro - inverso peptide RICK retained the main unique properties of CADY-K such as conformational versatility, formation of RICK:siRNA nanoparticles and remarkable efficacy in siRNA cellular delivery. Interestingly, in contrast to other retro - inverso peptides [51, 62], we observed a structural difference concerning the tryptophan cluster between CADY-K ( l -isomer), d -cady-k ( d -(isomer) and RICK, highlighting the important role of this amino acid. Moreover, because tryptophan has emerged as an important amino acid for membrane translocation [63, 64], a tryptophan clustering is a potential feature that should be taken into account for future PBN designs.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Our results revealed that this retro - inverso peptide RICK retained the main unique properties of CADY-K such as conformational versatility, formation of RICK:siRNA nanoparticles and remarkable efficacy in siRNA cellular delivery. Interestingly, in contrast to other retro - inverso peptides [51, 62], we observed a structural difference concerning the tryptophan cluster between CADY-K ( l -isomer), d -cady-k ( d -(isomer) and RICK, highlighting the important role of this amino acid. Moreover, because tryptophan has emerged as an important amino acid for membrane translocation [63, 64], a tryptophan clustering is a potential feature that should be taken into account for future PBN designs.…”
Section: Discussioncontrasting
confidence: 74%
“…In sum, we demonstrated through three approaches that RICK is more stable against proteolysis phenomena (trypsin or serum) compared to CADY-K. To our knowledge, only Seelig and Coll are working on retro - inverso CPP in a non-covalent strategy (riDOM:plasmid) [51, 52]. However, they did not look at trypsin or serum resistance of their peptide.…”
Section: Resultsmentioning
confidence: 99%
“…Retroinverso melittin has fused to dioleoyl phosphoethanolamine for making a gene therapy vehicle riDOM, which has DNA binding as well as cell penetrating properties. Milletin has cell penetration properties whereas dioleoyl phosphoethanolamine binds DNA (Ngoei et al, 2013;Québatte, Kitas, & Seelig, 2013).…”
Section: And Simulation Studies On Retroinverso Peptidomimeticsmentioning
confidence: 99%
“…The same could apply of PF/NFs, as they are also quite hydrophobic. A similar layer theory was proposed by Québatte et al., 44 where the authors speculated that a portion of riDOM, their developed CPP, is not involved in DNA binding and will instead bind to a sulfated GAG, thereby starting an endocytotic translocation process. Nanoparticles formed with CPPs have been reported to use scavenger receptors for internalization and also interact with heparin sulfate proteoglycans,13, 14, 15, 24, 45 indicating the presence of CPP able to interact with cell membrane structures.…”
Section: Discussionmentioning
confidence: 99%